Effects of vest loading on sprint kinetics and kinematics - Cross, M. R.; Brughelli, M. E.; Cronin, J. B. (The Journal of Strength and Conditioning Research, 2014)
The effects of vest loading on sprint kinetics and kinematics during the acceleration and maximum velocity phases of sprinting are relatively unknown. A repeated measures analysis of variance with post hoc contrasts was used to determine whether performing 6-second maximal exertion sprints on a nonmotorized force treadmill, under 2 weighted vest loading conditions (9 and 18 kg) and an unloaded baseline condition, affected the sprint mechanics of 13 males from varying sporting backgrounds. Neither vest load promoted significant change in peak vertical ground reaction force (GRF-z) outputs compared with baseline during acceleration, and only 18-kg loading increased GRF-z at the maximum velocity (8.8%; effect size [ES] = 0.70). The mean GRF-z significantly increased with 18-kg loading during acceleration and maximum velocity (11.8-12.4%; ES = 1.17-1.33). Horizontal force output was unaffected, although horizontal power was decreased with the 18-kg vest during maximum velocity (-14.3%; ES = -0.48). Kinematic analysis revealed decreasing velocity (-3.6 to -5.6%; ES = -0.38 to -0.61), decreasing step length (-4.2%; ES = -0.33 to -0.34), increasing contact time (5.9-10.0%; ES = 1.01-1.71), and decreasing flight time (-17.4 to -26.7%; ES = -0.89 to -1.50) with increased loading. As a vertical vector-training stimulus, it seems that vest loading decreases flight time, which in turn reduces GRF-z. Furthermore, it seems that heavier loads than that are traditionally recommended are needed to promote increases in the GRF-z output during maximum velocity sprinting. Finally, vest loading offers little as a horizontal vector-training stimulus and actually compromises horizontal power output.